A variação sintática da negação na fala culta de Fortaleza-CE - Oliveira, Ana Carine Maia de (2022)
This research aims to analyze the syntactic variation of negative sentences in educated Portuguese spoken in Fortaleza. The structure [Neg + V] is considered a standard variant of the phenomenon, while the structures [Neg + V + Neg] and [V + Neg] are the innovative variants of negative sentences in Brazilian Portuguese (BP). In the light of Variations Sociolinguistics, or Labovian, which understands that variation is a process belonging to the linguistic system and that is motivated by both structural and social aspects (LABOV, 2008), and using the sample obtained by the Project Description of Oral Portuguese Cult of Fortaleza (PORCUFORT), a project based at the State University of Ceará (UECE), aims to answer the following guiding question: how do educated speakers in the city of Fortaleza structure their negative propositions? The independent variables of this study are composed of factors: a) social: sex and age; and b) syntactic: type of clause (absolute, coordinate and subordinate), verb structure (simple and verbal periphrasis), verb tense (present, past and future), type of subject (explicit, implicit and non-existent), type of sentence (answer, question and present in the chain of discourse) and presence/absence of other negative terms - nothing, nobody, none, nor, never, nor anything - (absence and presence). The study made use of the Goldvarb X statistical program (SANKOFF; TAGLIAMONTE; SMITH, 2005) to identify which factors internal and external to the linguistic structure influence the realization of the phenomenon investigated here. The results obtained showed that the variation in the sentence denial of educated speech in Fortaleza is essentially conditioned by factors internal to the linguistic system, with the variables type of subject, type of sentence, presence or absence of negative word and type of sentence being the groups of factors that influence the realization of innovative variants.